Wood anatomy of Gentianaceae, tribe Helieae, in relation to ecology, habit, systematics, and sample diameter - Carlquist, Sherwin; Grant, Jason (My University, 2005)
Twenty collections representing one species each of Symbolanthus and Tachia, and 17 species of Macrocarpaea were studied by means of light microscopy and scanning electron microscopy (SEM). Wood details show that the three genera form a coherent group; Tachia differs from the others in only a few minor characters. Because the species studied form a natural group, wood variations within Helieae offer the basis for correlations and interpretations with respect to habit and ecology. Diameter of stems studied proves to be an important variable that must be taken into account. Correlations with stem diameter include wider vessels in outer wood of wider samples. This would correspond to deeper penetration of reliable water tables by roots of helioid trees or large shrubs. Ray height decreases with increase in stem diameter, an indication of paedomorphosis. Rays of all species are paedomorphic in histology by virtue of relative paucity or even absence of procumbent cells in multiseriate rays. Pseusoscalariform lateral wall pitting of vessels is also a feature characteristic of paedomorphosis. The assemblage of paedomorphic features correlates well with the conclusion, reached by authors who used cladistic methods, that Gentianaceae other than Gentianeae are derived from suffrutescent prennials. The Mesomorphy Ratio, which incorporates three vessel features, correlates with leaf length and with stem diameter. All Helieae are mesophytic, but to various degrees. Septate fiber-tracheids, where present, are typically near vessels and form a substitute for or an addendum to vasicentric axial parenchyma as a mechanism for photosynthate storage. Vestured pits occur on lateral wall pits of vessels of all Helieae, but not on the fibertracheids. Vestured pits show diversity within Macrocarpaea, a feature of possible systematic significance.
Keywords: comparative wood anatomy; ecological wood anatomy; fiber-tracheids; Gentianaceae; Heliaeae; Macrocarpaea; paedomorphosis; sample diameter; vestured pits